2007
DOI: 10.1111/j.1462-2920.2007.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative distribution of presumptive archaeal and bacterial nitrifiers in Monterey Bay and the North Pacific Subtropical Gyre

Abstract: The recent isolation of the ammonia-oxidizing crenarchaeon Nitrosopumilus maritimus has expanded the known phylogenetic distribution of nitrifying phenotypes beyond the domain Bacteria. To further characterize nitrification in the marine environment and explore the potential crenarchaeal contribution to this process, we quantified putative nitrifying genes and phylotypes in picoplankton genomic libraries and environmental DNA samples from coastal and open ocean habitats. Betaproteobacteria ammonia monooxygenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

77
535
12
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(636 citation statements)
references
References 60 publications
77
535
12
1
Order By: Relevance
“…The ratio of AOA to AOB was larger than 1 at about 75% of the sites, and the greatest value of this ratio was primarily observed in the Hengshui and Xingtai reaches. In the natural environment, AOA are generally more abundant than AOB (Wessén et al, 2011;Leininger et al, 2006;Wu et al, 2010), and the abundance of AOA (Mincer et al, 2007) and AOB (Stehr et al, 1995) in the water column is commonly in the range of 10 2 to 10 5 gene copies/mL, which is consistent with the results of the present study.…”
Section: Physicochemical Characteristicssupporting
confidence: 82%
“…The ratio of AOA to AOB was larger than 1 at about 75% of the sites, and the greatest value of this ratio was primarily observed in the Hengshui and Xingtai reaches. In the natural environment, AOA are generally more abundant than AOB (Wessén et al, 2011;Leininger et al, 2006;Wu et al, 2010), and the abundance of AOA (Mincer et al, 2007) and AOB (Stehr et al, 1995) in the water column is commonly in the range of 10 2 to 10 5 gene copies/mL, which is consistent with the results of the present study.…”
Section: Physicochemical Characteristicssupporting
confidence: 82%
“…The CN strains are also highly similar on the 16S and amoA level to abundant groups of open ocean archaea from a range of oceanic provinces including the Sargasso Sea, Fernandina Island and the coast of Africa as indicated by BLAST searches of the Global Ocean Survey dataset (Rusch et al, 2007). Previous amoAbased phylogenies of AOA have shown that water column-derived sequences fall into two clusters termed 'A' and 'B' (Francis et al, 2005) thought to represent a depth-dependent partitioning of AOA (Hallam et al, 2006;Mincer et al, 2007;Beman et al, 2008 (Wuchter et al, 2006), and estimates of in situ per-cell activity rates in the California Current (0.2-15 fmol cell À1 day À1 ) (Santoro et al, 2010).…”
Section: Phylogenymentioning
confidence: 94%
“…Mesophilic archaea are ubiquitous and abundant members of diverse marine environments including coastal waters (Mincer et al, 2007;Beman et al, 2010), marine sediments, estuaries (Mosier and Francis, 2008;Bernhard et al, 2010;Urakawa et al, 2010), stratified basins (Coolen et al, 2007;Lam et al, 2007) and open ocean water columns (Beman et al, 2008;Church et al, 2010;Santoro et al, 2010). The recent cultivation of the first mesophilic marine archaeon, Nitrosopumilus maritimus, (Konneke et al, 2005;Martens-Habbena et al, 2009), two thermophilic archaea, Nitrosocaldus yellowstonii and Nitrosophaera gargensis (Hatzenpichler et al, 2008;de la Torre et al, 2008) and a freshwater archaeon, Nitrosoarchaeum limnia (Blainey et al, 2011) established that at least some of these organisms are chemolithoautotrophic ammonia oxidizers.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies suggest that AOA dominate in marine habitats (Wuchter et al, 2006;Mincer et al, 2007;Beman et al, 2008). In contrast, Mosier and Francis, (2008) found that copies of b-proteobacterial amoA were two orders of magnitude higher than archaeal amoA in high-salinity estuarine sediments.…”
Section: Introductionmentioning
confidence: 90%